Promoting Cultural Connectedness Through Indigenous-led Child and Family Services: A Critical Review with a Focus on Canada - Ball, Jessica; Benoit-Jansson, Annika (First Peoples Child & Family Review, 2023)
There is consensus that quality services to Indigenous children and families involve the transmission, preservation, and promotion of First Nations, Métis, and Inuit cultural connections and must be delivered within specific First Nations, Métis, and Inuit cultural frameworks led by Indigenous people. This view is expressed across research and service reports, in the Truth and Reconciliation Commission of Canada’s 2015 Report and Calls to Action, and in the Government of Canada’s newly enacted An Act Respecting First Nations, Inuit and Métis children, youth and families (2019). This article reviews support for this viewpoint, drawing from primarily Indigenous scholarship and illustrated with reference to Indigenous-led services across Canada.